Changes in the Salivary Proteome Associated With Canine Pyometra - Franco-Martínez, Lorena; Horvatić, Anita; Gelemanović, Andrea; Samardžija, Marko; Mrljak, Vladimir; Contreras-Aguilar, María Dolores; Martínez-Subiela, Silvia; Dąbrowski, Roman; Tvarijonaviciute, Asta (Frontiers in Veterinary Science, 2020)
The present study evaluated for the first time changes in the saliva proteome in bitches with pyometra through a high-throughput quantitative proteomic analysis. The aims were to explore whether saliva composition could reflect the physiopathological changes occurring in canine pyometra and to identify potential biomarkers of the disease. Saliva samples from six healthy (H) and six bitches with pyometra (P) were analysed using Tandem Mass Tags (TMT) - based approach. Additionally, fifteen samples were used for the validation of changes in haptoglobin concentration in saliva of dogs with pyometra. Proteomic analysis quantified 707 proteins in saliva. Comparison of the two groups revealed 16 unique proteins significantly modulated in saliva, with S100A calcium-binding protein 12 (S100A12), vimentin and haptoglobin (Hp) the most up-regulated in canine pyometra. According to Protein Analysis Through Evolutionary Relationships (PANTHER) classification tool, these proteins are mainly related to pro-inflammatory mediators, acute phase proteins and sepsis. In conclusion, it can be stated that there are changes in various proteins in saliva in canine pyometra reflecting different physiopathological changes occurring in this disease. These proteins could be a source of potential non-invasive biomarkers for this disease that should be confirmed in future studies.